PENGARUH KEPUASAN KERJA, MOTIVASI, DAN BEBAN KERJA TERHADAP KINERJA PADA PT. XX - WANANDA, REZMA; SANTOSO, WAWA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study was to determine the effect of several variables such as job satisfaction, work motivation and workload on employee performance. Research using quantitative methods is descriptive. The type of data used is primary data. This study uses a non-probability sampling method using a saturated sampling technique and totals 117 employees. The analytical method used is multiple linear regression. The results showed that job satisfaction had no effect on employee performance, while work motivation and workload had an effect on employee performance.